Bioinspired functional mimics of the manganese catalases - Signorella, Sandra Rosanna (2012)
Catalase enzymes are present in most aerobic forms of life and are responsible for the decomposition of hydrogen peroxide to molecular oxygen and water. Although most catalases contain the iron-protoporphyrin IX prosthetic group, some bacteria utilize a non-heme manganese containing catalase (MnCAT). The active site of these enzymes contains two Mn ions triply bridged by a 1,3-carboxylato from a Glu residue and two solvent-derived single atom bridges. Determination of their exact catalytic mechanism is precluded by their fast kinetics. Hence biomimetic compounds may help providing valuable insights into the mechanisms of these enzymes. Indeed, comparison of the activity of structurally characterized complexes can help delineating the functional roles of the bridging ligands and structural motifs that play a key function in H2O2 disproportionation. Moreover, due to the potential use as catalytic scavengers of H2O2 for preventing oxidative stress injuries, numerous and diverse Mn compounds have been reported to have CAT-like activity. The present review is focused on non-porphyrinic mimics of MnCAT. Several families of Mn-based catalysts are described, the properties of which are commented on, stressing the role of bridging and terminal ligands on redox potentials and catalysis.